Factors Affecting the Implementation of SAK EMKM in MSMEs Registered in PLUT Sleman Regency - Wijayanti, Wahyu; Wulandari , Ika (Etihad: Journal of Islamic Banking and Finance, 2024)
Introduction: Sleman Regency is home to many established and expanding MSMEs. However, many of them do not follow SAK EMKM while preparing financial accounts, and many are simply unaware of SAK EMKM. This study aims to ascertain how PLUT Sleman Regency members prepare financial statements based on SAK EMKM in relation to business size, education level, information availability, and socialization. Research Methods: This study is a quantitative research with a sample determination method using the slovin formula and analyzed using multiple linear regression analysis. Results: The study's findings demonstrate that the preparation of financial statements using SAK EMKM is unaffected by the company's size. The creation of financial statements by SAK EMKM is affected by educational background, information availability, and socialization. Conclusion: The findings of this study have significance for relevant organizations like the Cooperative and SME Office, which must create a training curriculum to enhance MSME actors' knowledge and proficiency in creating financial reports using SAK EMKM. Additionally, MSME actors can receive training in financial statement preparation in compliance with SAK EMKM and enhance their accounting knowledge.